Effects of hyperthyroidism on serum alanine amino transferase and alkaline phosphatase levels in liver - Suma, Sunjida Akter; Akhter, Qazi Shamima (Journal of Bangladesh Society of Physiologist, 2021)
Background: Hyperthyroidism is one of the most common endocrine disorders. Thyroid hormones are essential for normal metabolic function of body cells including the liver cells. Again, metabolism of thyroid hormones takes place in liver. Therefore, hyperthyroidism may affect liver cells and causes change in hepatic enzymes level. Objective: To assess serum alanine aminotransferase (ALT) and alkaline phosphatase (ALP) levels in hyperthyroid patients. Methods: This cross sectional study was conducted in the Department of Physiology of Dhaka Medical College from July 2016 to June 2017. Total number of 50 subjects of both sexes aged from 18 to 50 years were selected. Among them, 25 hyperthyroid patients were considered as the study group (B) and 25 age matched healthy subject were considered as control group (A). Serum ALT and ALP were estimated in the Biochemistry & Molecular Biology Department of BSMMU. For statistical analysis, Unpaired student’s ‘t’ test and Chi Square test were done. Results: Serum ALT and ALP levels were significantly (p<0.001) increased in patients suffering from hyperthyroidism. Conclusions: This study showed that detection of changes in serum hepatic enzymes in hyperthyroidism useful for prediction of developing liver disease. J Bngladesh Soc Physiol 2021;16(1): 44-48